A MULHER DEVE SER BELA, DEVE TER GRAÇAS E ENCANTOS : educação de salão na São Luís republicana (1890-1920) - Silva, Camila Ferreira Santos (2011)
The passage of the nineteenth to the twentieth century gave birth in São Luís-MA a climate of hope, based on republican discourse of progress. The scenery of this city, until the mid-nineteenth century, had characteristics slave and rural, the switch to a modern city, caused several changes not only political, economic and structural, but also social. And to adapt to this new scenario was the need that the population, in general, acquired habits and behaviors consistent with the purpose of civilizing and modernizing the time. It is this path that the present research seeks to analyze the education received by women lounge, particularly women from the middle and upper strata of society ludovicense. Since these transformations, as well as charges related to the symbols of "civility" and "modernity", focused mainly on women, which was necessary to retain the "eternal" feminine qualities such as gentleness, modesty, among others, enhanced through newspapers, magazines and manuals of civility and etiquette. In this sense, it was essential to keep the woman attributes such as marriage, motherhood, beauty, being trendy, relevant, above all, their social class elite, and still have school education, and especially "education room" in order to and be prepared to play the roles of wife, mother and homemaker. The study reveals that in addition to these roles, she should represent her family socially through behavioral practices that highlighted the "good manners" as a means of obtaining prestige and distinction. To this end, this study guide the following categories: modernity (Baudelaire, 1996; Hall, 1998), civilization (Elias, 1994, Starobinski, 2001), etiquette (Elias, 2001), distinction (Bourdieu, 2007) and gender (Bourdieu, 1999, Scott, 1996). For this purpose, we use sources the newspapers, the Elegant Magazine, civility and etiquette manuals and literary works, present at the Public Library Benedito Leite and Public Archives of Maranhão.